2013
DOI: 10.1016/j.bjid.2012.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia severity index compared to CURB-65 in predicting the outcome of community acquired pneumonia among patients referred to an Iranian emergency department: a prospective survey

Abstract: CURB-65 seems to be the preferred method to predict mortality and need for ICU admission in patients with community-acquired pneumonia. Despite their comparable specificity and sensitivity, CURB-65 is much easier to implement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…8 A Brazilian study by Alavi-Moghaddam M et al infers that CURB-65 showed a better predictive value in foreseeing both the need for ICU admission and mortality than PSI. 16 An Egyptian study by Eldaboosy SAM et all showed the ability to predict ICU admission was higher for SIPF score compared to PSI and CURB-65 and says SIPF is useful to predict mortality in CAP. 17 But neither of these studies had compared PSI, CURB 65 with IDSA/ATS Scoring system making our study more unique and our study shows that IDSA/ATS scoring system a better scoring system in Indian health care setting and can be used in Indian health care.…”
Section: Analysis Of Scoring Systemsmentioning
confidence: 99%
“…8 A Brazilian study by Alavi-Moghaddam M et al infers that CURB-65 showed a better predictive value in foreseeing both the need for ICU admission and mortality than PSI. 16 An Egyptian study by Eldaboosy SAM et all showed the ability to predict ICU admission was higher for SIPF score compared to PSI and CURB-65 and says SIPF is useful to predict mortality in CAP. 17 But neither of these studies had compared PSI, CURB 65 with IDSA/ATS Scoring system making our study more unique and our study shows that IDSA/ATS scoring system a better scoring system in Indian health care setting and can be used in Indian health care.…”
Section: Analysis Of Scoring Systemsmentioning
confidence: 99%
“…However, of 40 studies included in a systematic review of articles published between 1980 and 2009 [14], only one study was derived from a LMIC. Given the paucity of evidence, recent validation efforts in new settings are welcome [15]. The SWAT-Bp (male Sex, Wasting, non-Ambulatory, Temperature, Blood pressure) score was derived from an inpatient population in Malawi where CRB-65 performs less well than in Europe [5].…”
Section: Severity Scores For Community Acquired Pneumonia (Cap) Armentioning
confidence: 99%
“…Although these three scores perform equally well among patients with CAP to predict mortality, 10 CURB-65 is easier to implement in clinical practice. 11 In some studies CURB-65 score was not found as a good predictor of adverse outcome 12 or early mortality 13 in CAP. However, according to many other studies, patients with a higher CURB-65 score had a greater chance for in-hospital mortality 14 and 30-day mortality [15][16][17] because of pneumonia.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to CURB‐65, the pneumonia severity index (PSI) is utilised to predict the prognosis of CAP. Although these three scores perform equally well among patients with CAP to predict mortality, CURB‐65 is easier to implement in clinical practice . In some studies CURB‐65 score was not found as a good predictor of adverse outcome or early mortality in CAP.…”
Section: Discussionmentioning
confidence: 99%